ANALYZING THE E-BUSINESS TOWARD SUPPLY CHAIN PROCESS (CASE STUDY: FASHION ONLINE SHOP IN MANADO) - Tangel, Anastasia G.S; Pangemanan, Sifrid S. (Universitas Sam Ratulangi, 2019)
Abstract : One major benefit of e-business is the ability to more efficiently manage the supply chain. Many companies are using e-business and its related components to facilitate supply chain management. The firms are realizing a variety of benefits such as information integration, planning synchronization, workflow coordination and new business model. The purpose of this study is to analyze e-business towards supply chain process. Case Study on Fashion Online Shop in Manado and if those variables are already been applied at the business. This research is using qualitative approach through interview. The population of this research is 10 owners of fashion online shop in Manado. Based on the results of the analysis it was found that e-business toward supply chain measured by information integration, planning synchronization, workflow coordination and new business model have a positive effect against the fashion online shop. Based on the result, by using the components of e-business, companies can work directly with suppliers and manufacturers, allowing them to eliminate the intermediary costs of distributionKeywords : e-business, supply chain process